Optimizing Omnichannel Strategies for MSME-Scale F&B Businesses in Makassar - Ipahriani Rahman; A Ifayani Haanurat; Andi Mappatompo Badawi (www.amertainstitute.com, 2025)
This study aims to optimize omnichannel marketing strategies for MSME-scale F&B businesses in Makassar, with a focus on the implementation of sales and marketing channels (both offline and online), eliminating challenges and opportunities in omnichannel integration, and formulating effective optimization strategies to improve customer experience and business performance. The results of the study indicate that omnichannel strategies are able to increase customer interaction, operational efficiency, and sales conversion, as well as build connections and engagement with target audiences. Key factors contributing to the success of this strategy include the use of social media, big data, artificial intelligence (AI), and effective integration systems. However, omnichannel implementation faces challenges such as the complexity of technology integration and the need for large investments. This study concludes that the quality of omnichannel strategies can provide a competitive advantage in the digital market and increase customer loyalty through consistent and satisfying experiences.